2008
DOI: 10.1038/nsmb.1460
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the RNA polymerase II C-terminal domain dictates transcription termination choice

Abstract: Cryptic unstable transcripts (CUTs) are short, 300-600-nucleotide (nt) RNA polymerase II transcripts that are rapidly degraded by the nuclear RNA exosome in yeast. CUTs are widespread and probably represent the largest share of hidden transcription in the yeast genome. Similarly to small nucleolar and small nuclear RNAs, transcription of CUT-encoding genes is terminated by the Nrd1 complex pathway. We show here that this termination mode and ensuing CUTs degradation crucially depend on the position of RNA poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(154 citation statements)
references
References 55 publications
7
146
1
Order By: Relevance
“…Nrd1 directly interacts with the transcription complex by binding Ser-5p and the nascent RNA through its CID and RRM domains, respectively, 62 whereas Ser-2 phosphorylation is antagonistic to Nrd1 binding and Nrd1 function in early termination. 63 Ser-2 phosphorylation is important for proper termination and pre-mRNA processing of gene transcripts. 64 The lack of Ser-2p dependent activities upstream of promoters leads us to believe that promoters contain information that leads to asymmetric delivery of the P-TEFb/ctk1 kinase (Fig.…”
Section: One Way or Another?mentioning
confidence: 99%
“…Nrd1 directly interacts with the transcription complex by binding Ser-5p and the nascent RNA through its CID and RRM domains, respectively, 62 whereas Ser-2 phosphorylation is antagonistic to Nrd1 binding and Nrd1 function in early termination. 63 Ser-2 phosphorylation is important for proper termination and pre-mRNA processing of gene transcripts. 64 The lack of Ser-2p dependent activities upstream of promoters leads us to believe that promoters contain information that leads to asymmetric delivery of the P-TEFb/ctk1 kinase (Fig.…”
Section: One Way or Another?mentioning
confidence: 99%
“…After Nrd1-dependent termination by RNAPII, CUTs are rapidly polyadenylated by the TRAMP complex, and then degraded by the nuclear exosome (Wyers et al 2005;Arigo et al 2006b;Houalla et al 2006;Thiebaut et al 2006). Recently, Gudipati et al (2008) showed that Nrd1-dependent termination of CUTs is inhibited by CTD phosphorylation on Ser2 and promoted by Ser5 phosphorylation. They also showed that binding of Nrd1 to the nascent transcript, even if not sufficient, is necessary for efficient termination.…”
Section: A Wider Role For the Nrd1 Complex In Gene Expressionmentioning
confidence: 99%
“…The studies of Gudipati et al (2008) and Vasiljeva et al (2008a) provide an explanation of why termination depends on the distance traveled by RNAPII, and how RNAPII chooses between the 39 cleavage and polyadenylation pathway for mRNA termination and the Nrd1 complex for noncoding RNAs, short ORFs and CUT termination. Short transcripts are mostly associated with Ser5 phosphorylation, which recruits the Nrd1 complex.…”
Section: A Wider Role For the Nrd1 Complex In Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the choice of termination pathway in budding yeast is influenced at least in part by the relative densities of Serine 5 and 2 phosphorylation (Ser5p and Ser2p) on the CTD [24]. Ser5p is higher at the beginning of the transcription cycle favouring termination by Nrd1.…”
Section: The Role Of Xrn2 In Termination At Other Pol II Gene Classesmentioning
confidence: 99%